Hairy elbows: A case study - Fernandez-Crehuet, Pablo; Ruiz-Villaverde, Ricardo; Serrano, Jose Luis Fernandez-Crehuet (Australian family physician, 2013)
A boy aged 6 years was referred to our clinic for evaluation of the presence of fair, thin hair on both of his elbows. This condition had first been observed when he was 2 years of age and the hair had subsequently increased in length and thickness. He had a history of asthma and was being treated by a paediatrician. His family medical record was otherwise unremarkable.